2022
DOI: 10.7554/elife.72381
|View full text |Cite
|
Sign up to set email alerts
|

A mechano-osmotic feedback couples cell volume to the rate of cell deformation

Abstract: Mechanics has been a central focus of physical biology in the past decade. In comparison, how cells manage their size is less understood. Here we show that a parameter central to both the physics and the physiology of the cell, its volume, depends on a mechano-osmotic coupling. We found that cells change their volume depending on the rate at which they change shape, when they spontaneously spread are externally deformed. Cells undergo slow deformation at constant volume, while fast deformation leads to volume … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(111 citation statements)
references
References 79 publications
8
90
0
Order By: Relevance
“…(3) Balance of ionic fluxes: the typical timescales of ion relaxation observed during a cell regulatory volume response after an osmotic shock are of the order of a few minutes [16], [25]. Together, this means that our quasi-static theory is designed to study cell size variations on timescales larger than a few minutes.…”
Section: Resultsmentioning
confidence: 99%
“…(3) Balance of ionic fluxes: the typical timescales of ion relaxation observed during a cell regulatory volume response after an osmotic shock are of the order of a few minutes [16], [25]. Together, this means that our quasi-static theory is designed to study cell size variations on timescales larger than a few minutes.…”
Section: Resultsmentioning
confidence: 99%
“…In single cells, it has been recently shown that when tension increases, the volume drops, and, interestingly, this response is inverse to the one we observed and still occurs with transient dynamics as observed in this study. This behavior is explained by a mechano-osmotic coupling—which involves actin cortex, ion fluxes, and membrane tension—and with the timescale of cell shape deformation that is inversely proportional to the amplitude of volume change ( Venkova et al., 2022 ). This is consistent with our observation of a peak of cell volume increase following a rapid bending of less than 10 s. It is also consistent with the fact that a slow membrane tension decrease in PalmC-treated cells did not change the cell volume.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cell volume has recently been tied to substrate stiffness and adherence, engaging in a feedback system with YAP/TAZ (Gonzalez et al, 2018). Interestingly, several studies suggest that actomyosin contractility during cell spreading can also reduce cell volume through the expulsion of water, concentrating cell constituents (Guo et al, 2017; Venkova et al, 2021; Xie et al, 2018). Large cell lines may activate cytoskeletal signalling to concentrate key biosynthetic regulators and sustain growth.…”
Section: Discussionmentioning
confidence: 99%